Effects of tree age on flavonoids and antioxidant activity in Torreya grandis nuts via integrated metabolome and transcriptome analyses. Issue 1 (17th January 2023) - Yan, Jingwei; Zeng, Hao; Chen, Weijie; Zheng, Shan; Luo, Jiali; Jiang, Huifeng; Yang, Baoru; Farag, Mohamed A.; Lou, Heqiang; Song, Lili; Wu, Jiasheng
Abstract: The nuts of Torreya grandis are abundant in flavonoids, providing potential antioxidant activity. Considering that T. grandis can yield nuts for hundreds or thousands of years, effects of tree age on flavonoids and antioxidant activity of T. grandis nuts were targeted in this study for the first time. Results revealed that antioxidant activity and total flavonoid contents in 100‐ and 1000‐years‐old T. grandis nuts were much higher compared to 10‐years‐old T. grandis . The content of 19 flavonoids showed significant correlations with antioxidant activity in 100‐ and 1000‐years‐old trees using metabolites profiling. Transcriptome and coexpression analysis indicated that seven genes were associated with aged‐related flavonoids biosynthesis. Further analysis showed that abscisic acid and gibberellin might regulate the age‐related differential flavonoids accumulation. Our study provides a novel viewpoint that aged T. grandis is likely to present a better source of natural antioxidants and has yet to be examined in other tree models. Abstract : This study identify targeted flavonoids at different tree age of T. grandis known to exert strong antioxidant activity and health benefits. The antioxidant activity and the total flavonoid contents in 10‐years‐old T. grandis were lower compared to those in 100‐ and 1000‐years‐old T. grandis. The contents of 19 flavonoids showed significant correlations with antioxidant activity in 100‐ and 1000‐years‐old trees and coexpression analysis indicated that 7 key genes were associated with aged‐related flavonoids biosynthesis in T. grandis nuts.